Penerapan Model Pembelajaran Moving Class Terhadap Efektifitas Belajar Siswa - Riandi Riandi; Rizdki Elang Gumelar (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
This study aims to determine the effect of the application of moving class learning models on the effectiveness of student learning "in MTs state Serang . The number of samples is 30 students, the method used by the writer in conducting this research descriptive survey, with data collection techniques: observation, interviews, questionnaires, documentation and literature study. Based on the data the writer obtained from the results of the study were normally distributed with a mean value: 38.43, median: 38.83, mode: 39.63 and standard deviation: 5.84. whereas in variable Y or learning effectiveness students are normally distributed with a mean value: 39.47, median: 40.37, mode: 42.17 and standard deviation: 8.23. In this study the writer concluded that there is a high enough influence on the moving class learning model on student learning effectiveness because it obtained the correlation coefficient ("r") of rxy: 0.76 with a contribution rate of 58% and the remaining 48% influenced by other factors which can affect the effectiveness of student learning.